Pengembangan Potensi Wisata Agro di Kawasan Condet Kelurahan Balekambang Jakarta Timur - Nahri Nurul Azriati; Devi Roza K. Kausar (Fakultas Pariwisata Universitas Pancasila, 2018)
Jakarta as tourist destinations in Indonesia to implement various types of travel include cultural, historical and ecotourism. For examples of nature tourism in Jakarta is the issue of potential development of the Ciliwung River as a nature-based tourist destination. One segment which is a conservation area in the Watershed is Fruit of Condet, East Jakarta. Lahan Buah Condet is the only farm remaining pockets of the vast Condet set at DCI Jakarta Governor Decree No.DIV-1511/E/74. Potential tread such as endemic plants typical namely Salak and Duku Condet. Their Jakarta Governor Decree No. 646 2016 to further accelerate the implementation of the settlement and development of Lahan Buah Condet as a tourist destination as well as agrotourism area in East Jakarta. Problems in development of agrotourism is limited plantations, easily flooded, access to the plantations in the housing area residents and utilization of spatial patterns that are less well maintained, it is feared to cause damage to plantations. This research used qualitative method. By combining variable of agrotourism, conservation, and considering the potential of the land, found a solution how the concept of agrotourism in the form attractions, accessibilities, amenities, ancillary and institutions in Lahan Buah Condet can be suitable with the concept of consideration factors for agro tourism development.